An Output Instruction Based PLC Source Code Transformation Approach For Program Logic Simplification - Ghosh, Arup; Qin, Shiming; Lee, Jooyeoun; Wang, Gi-Nam (Informatica, 2017)
Due to the growing size and complexity of the PLC (Programmable Logic Controller) programs used for controlling the industrial processes, there is an increasing need for an approach that can help the users to understand the control logics of the PLC programs easily, and can assist them to analyze the programming errors effectively. In this paper, we propose an approach that takes the source code file of PLC program as the input; and transforms it into a hierarchical-structured XML (extensible markup language) file. The XML file format is based on the PLC output instructions and their corresponding conditions. It helps the users to identify the actual cause of a programming error quickly. In addition, a novel technique is applied that decomposes the PLC program into several smaller and modular sub-logic blocks. This makes the control logic simpler and easier to follow. An additional software application has also been developed for state-based graphical visualization of the XML file.